Analysis of Competence Factors, Teamwork, and Work Motivation on the Optimization of Performance of Yonko 462 Kopasgat Enlisted Personnel - Fahriyansyah, Muhammad Iqbal; Sadipung, Theresia Oktavia (Dinasti International Journal of Management Science, 2025)
Military personnel performance plays a vital role in supporting an organization’s success in achieving strategic goals. Initial observations at Tamtama Kompi B Yonko 462 Kopasgat identified challenges such as inadequate competence, ineffective teamwork, and low work motivation, which hinder optimal performance. Therefore, an in-depth analysis is required to understand how these factors influence personnel performance. This study aims to examine the impact of competence, teamwork, and work motivation on personnel performance at Tamtama Kompi B Yonko 462 Kopasgat. The research uses a quantitative method with a descriptive approach. Data were collected through performance assessments, competence evaluations, teamwork analyses, and motivation surveys between 2021 and 2023. The results show that competence significantly improves individual performance quality, as well as teamwork, which fosters synergy and enhances task execution. Furthermore, high work motivation plays a key role in encouraging personnel to contribute their best efforts. These findings emphasize the importance of strengthening competencies, improving teamwork, and maintaining high motivation levels to enhance overall organizational performance. The study highlights the need for focused interventions to address these key factors to ensure optimal personnel performance in the military organization.